2023
DOI: 10.1200/jco.22.01142
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Adjuvant Hepatic Arterial Infusion Chemotherapy With FOLFOX in Hepatocellular Carcinoma With Microvascular Invasion: A Multicenter, Phase III, Randomized Study

Abstract: PURPOSE To report the efficacy and safety of postoperative adjuvant hepatic arterial infusion chemotherapy (HAIC) with 5-fluorouracil and oxaliplatin (FOLFOX) in hepatocellular carcinoma (HCC) patients with microvascular invasion (MVI). PATIENTS AND METHODS In this randomized, open-label, multicenter trial, histologically confirmed HCC patients with MVI were randomly assigned (1:1) to receive adjuvant FOLFOX-HAIC (treatment group) or routine follow-up (control group). The primary end point was disease-free sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 31 publications
0
37
0
Order By: Relevance
“…Adjuvant HAIC with FOLFOX significantly improved RFS with acceptable toxicity in HCC patients with MVI. 55 However, these findings need to be confirmed by further trials.…”
Section: Unanswered Questions Of Adjuvant Treatmentmentioning
confidence: 95%
“…Adjuvant HAIC with FOLFOX significantly improved RFS with acceptable toxicity in HCC patients with MVI. 55 However, these findings need to be confirmed by further trials.…”
Section: Unanswered Questions Of Adjuvant Treatmentmentioning
confidence: 95%
“…Moreover, the strong antitumor efficacy for intrahepatic lesions enabled FOLFOX-HAIC as a conversion therapy to transform unresectable HCC to resectable one [63]. And a recent study reported that 1-2 cycles of FOLFOX-HAIC in the adjuvant setting significantly improved recurrence free survival (RFS) for patients with microvascular invasion [64].…”
Section: Intra-arterial Therapiesmentioning
confidence: 99%
“…Adjuvant therapy may provide survival bene ts for HCC patients with MVI(19). A recent clinical trial showed that adjuvant HAIC with FOLFOX largely improved the disease-free survival bene ts in HCC patients with MVI(20). Our study provided a comprehensive landscape of HCCs with MVI, which might give new clues for exploring novel immunotherapies for HCC patients with MVI.MVI is likely to progress into IM, Wang et al reported that IM patients had worse prognoses compared with MO patients after liver transplantation(21).…”
mentioning
confidence: 99%